Appreciation of Nature in Architecture: Interaction between Topography & Design in the Case of Karmi (Karaman) Village, North Cyprus - Khani, Arezoo (Eastern Mediterranean University EMU, 2015)
One of the main problems of contemporary architecture is the segregation of human life from the natural environment due to rapid change of science and technology. Studies on the essences in the interaction of man and environment could be possible through historical and vernacular settlements, where the dynamics of nature and peculiarities of human beings are exceedingly regarded during the production of the built environment. In this research, Karmi (Karaman) village, a vernacular settlement in North Cyprus, is selected as the case study to analyse and illustrate the relationship between nature and man in general, and the interaction between topography and design in particular. In this study on the building traditions, used in this village, are intended to review of organic concepts in architectural design and provide a reference for contemporary designers and introduce them some of the concerns on organic approaches, make comparison of the architecture design concepts with the information gathered from the village (by personal observations of the researcher and interviews with the occupants of the village) highlighted some practical approaches at different scales of design, ranging from settlement to interior space scales. Although this village is almost a perfect model to be utilized as a source for designers, there are some recently constructed buildings totally conflicting with the traditional fabric of the settlement and boldy indicate harsh interfere of human being to the nature. Karmi village is considered an important source of knowledge and case illustrating how topography and building can interact and create settlements in harmony with nature. At the same time, it gives opportunities to monitor destructing implications in nature and to understand the differences between the environment, sensitive approaches and the over ignoring this important notion in contemporary times and designs. In North Cyprus, there is a serious problem due to the lack of sufficient concern in the use of the natural topography, especially since the "construction boom" in the early 2000s, especially in the region of Kyrenia where Karmi Village is located. There have been problematic matters in the world in finding the solution to save nature. Therefore, this research in the case of appreciation of nature focuses on the interaction of topography and the built environment. This study aims to clarify how architecture could affect and be affected by the environment, where buildings and nature are interacted as in the case of Karmi village in North Cyprus. Under aforementioned conditions, the authentic of urban pattern of Karmi Village, where determination has begun should be studied before it’s lost and putting toward the values of this pattern has a great importance. Under the guidance of these conditions, it is aimed to discuss and state, how architecture affected the environment and influenced by the environment by considering the case of Karmi Village. Keywords: Topography, Vernacular Architecture, Natural environment, Built environment, Karmi village, North Cyprus.

ÖZ: Çağdaş mimarinin temel sorunlarından biri, doğal çevre ve insan ilişkisinin, sözkonusu etkileşimin yeterince önemsemeyen bilim ve teknolojide olan değişikliker dolayısıyla kopmasidir. İnsan-çevreay etkileşimini esaslarının araştırılmasında, tarihsel ve yöresel yerleşimler – bu ollanlar doğadaki dinamizmin ve insan güdülerinin yapılaşmış çevrenin oluşumunda son derece etkili olduğunu gösteren yerlerdir – çok önemli bir yere sahiptir. Bu çalışmada, doğa ile insan ilişkisi ve topoğrafya ile tasarım etkileşimi genel olarak ele alınıp, Karmi (Karaman) köyü özelinde örneklenip açıklanmaktadır. Karmi Köyü, Kıbrıs’ın yöresel mimari dokusuna sahip, Beşparmak Dağları eteklerinde bir yerleşimdir. Yapılan bu araştırma ile hedeflenen, insan-çevre ilişkileri ve topoğrafya-tasarım etkileşimleri üzerinde bir farkındalık yaratıp, Karmi Köyü özelinde deneyimlenen yapı geleneklerinin çağdaş tasarımcılara bir referans oluşturması ve organik yaklaşımlar üzerine yol göstermektir. Köy sakinleri ile yapılan görüşmeler ve köy mimarisi üzerine yapılan gözlemler doğrultusunda, mimari tasarımda organik kavramların gözden geçirilmesi ve karşılaştırılması yapılmış; yerleşim ölçeğinden iç mekan ölçeğine kadar tasarımın farklı boyutlarında temel yaklaşımlar vurgulanmıştır. Köyde, yapılaşmış çevreye dair kullanılabilen mükemmele yakın bir model varken; yakın zamanda inşa edilen bazı binaların bu yerleşimin, geleneksel dokusunu tahrip ettiğini ve insanoğlunun doğaya nasıl aykırı bir müdahalede bulunduğunu göstermektedir. vi Bu noktada, Karmi köyü, topoğrafya ve bina etkileşiminin nasıl olduğunu ve doğa ile nasıl uyumlu bir tasarımın oluşturulabileceğini gösteren önemli bir kaynak olarak kabul edilebilir. Aynı zamanda, Karmi Köyü mevcut geleneksel dokusu ve yeni yapılaşmış çevresi ile, doğal çevreyi yok edici olumsuz etkileri tespit etmeyi, çevreye duyarlı yaklaşımları önemsemeyi ve günümüz mimarisinde bu önemli anlayışı görmezden gelen durumlara karşı bilinç geliştirmeye olanak sağlar. Karmi Köyü’nün uzun yıllar boyunca sahip olduğu geleneksel doku, Kuzey Kıbrıs'ta, özellikle Karmi köyünün de bulunduğu Girne bölgesinde, 2000'li yılların başında ortaya çıkan "inşaat patlaması" ile olumsuz etkilenmiş ve doğal çevresiye çeşitli müdahalelerde bulunulmuşture. Bu sürecin sonucunda da, topoğrafya-bina etkileşiminin çarpıcı örneklerine sahip yerleşimlerden biri olan Karmide bu durumdan ciddi bir şekilde olumsuz etkilenmiştir. Söz konusu bu şartlar altında, olumsuz etkilenmeye başlamış olan Karmi Köyü’nde özgün dokunun kaybolmadan çalışılması ve bu değerlerin ortaya konması büyük önem taşır. Tüm bunlar ışığında, bu çalışmada Karmi Köyü örneğinde mimarlığın çevreyi nasıl etkilediği ve mimarlığın çevreden nasıl etkilendiği tartışılarak açıklanmaktadır. Anahtar Kelimeler: Topoğrafya, Geleneksel Mimarlık, Doğal çevre, Yapılaşmış Çevre, Karmi Köyü, Kıbrıs.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2015. Supervisor: Prof. Dr. Hıfsiye Pulhan.
Keywords: Architecture Department; Architecture and Environment; Nature-Architecture-Karmi (Karaman) Village (Cyprus, North); Topography; Vernacular Architectures; Natural environment; Built environment; Karmi village; North Cyprus